The relationship between work family conflict and job performance at Pejabat Daerah Dan Tanah Maran, Pahang / Siti Saidah Halim - Halim, Siti Saidah (Faculty of Business Management, 2017)
The main objective of this research paper was to identify the types of work family conflict faced by the employees, to investigate the relationship between the work family conflict and job performance and to identify the level of the employee's job performance in Pejabat Daerah dan Tanah Maran, Pahang. The questionnaire was used as the instrument to collect data needed in order to complete this research paper. SPSS V-23 was used to analyse the questionnaire in order to determine the findings of the research. 76 of employees in Pejabat Daerah dan Tanah Maran were chosen as the respondents in the research conducted. This research paper used Stratified Sampling as the sampling technique. This research has three research objectives which are 0 identify the type of work family conflict faced by the employees, to investigate the relationship between the work family conflict and job performance and to identify the level of the employee's job performance and three research questions. There are relationship between work family conflict and job performance. The findings show moderate relationship between cooperative strategy and job performance among employees at Pejabat Daerah dan Tanah Maran. There are some recommendations that can be implementing by Pejabat Daerah dan Tanah Maran to achieve strong relationship between work family conflict and job performance in their organization.